Challenges on use of recreational parks in Kuala Lumpur - Mansor, Mazlina; Zakariya, Khalilah; Harun, Nor Zalina (Penerbit Universiti Sains Malaysia, 2019)
Recreational public parks in Kuala Lumpur are provided to support the leisure activities of city residents. The leisure activities include voluntary, recreation and social activities. Recreational parks have been recognised to play a positive reinforcement in promoting a healthy lifestyle, regarding physical health, social or even mental health. Nonetheless, some users have negative perceptions of recreational parks. The study investigates challenges pertaining to city residents' use and needs of recreational parks in Kuala Lumpur. Survey results from respondents who live in various zones in Kuala Lumpur were analysed to identify the parameters relevant for the study (n = 1617). The respondents' answers were statistically analysed using Statistical Package for the Social Science (SPSS). The findings revealed challenges related to the use and needs of recreational parks, namely facilities, design aspect, maintenance and safety. The findings imply that similar challenges are prominent in many research papers in the last 15 years. In other words, the specific challenges identified in this study need more attention, should be evaluated closely and be solved for future improvement on the conditions of the city's recreational parks. Through solving the pertinent aspects, comfortable spaces and activities that affect residents' health and well-being can be planned and managed.